CORPORATE SOCIAL RESPONSIBILITY DALAM MEMINIMALKAN PRAKTIK MANAJEMEN LABA - GAUTAMA SIREGAR, BUDI (IAIN Batusangkar, 2017)
Information earnings, a key element in the ?inancial statement, as stated in the Statement ofFinancial Accounting Concepts (SFAC) No. 2 is very important for those who use it because its predictivevalue. Earnings management can be applied in the preparation of ?inancial statements through creativeaccounting practices, the choice of accounting methods, the classi?ication of accounting systems andthe timing of the transaction. Earnings management practices can also done through the electionmethod of inventory accounting, depreciation of ?ixed assets, capitalization of pensions, in?lation, andamortization. Corporate Social Responsibility (CSR) activities disclosed by the company will give goodimpact for the company itself in the long term. The higher the company implemented corporate socialresponsibility, the lower the activity of management to manage earnings to its interests. Due to the?inancial statements prepared by the management will be read and analyzed by stakeholders as a basisfor decision making, management is required to prepare honest ?inancial statements. Disclosure ofcorporate social responsibility that is increasingly widespread will improve the image of the companyand increase of the pro?its to be earned by the company ultimately.